Acute Pharyngitis and Acute Laryngitis as Upper Respiratory Tract Infections: A Literature Review - Paradiesta, Andi Frieskha Naurah; Rachman, Amanda Azkiyah; Salsabila, Tsania Zulfa; Larasati, Anak Agung Ayu Regina; Rifki, Muhammad; Lestari, Rina (Jurnal Biologi Tropis, 2026)
Severe upper respiratory infections are a major health issue globally, including in Indonesia. Conditions like acute pharyngitis and acute laryngitis are frequently seen in medical settings and lead to many healthcare appointments. These illnesses vary in their causes, symptoms, diagnosis, and treatment, necessitating a thorough comprehension for the best patient care. This article aims to review various aspects of acute pharyngitis and acute laryngitis, including definition, etiology, epidemiology, pathophysiology, clinical manifestations, diagnosis, management, complications, prognosis, and prevention. A narrative literature review approach was employed using scientific sources obtained from Google Scholar, PubMed, ScienceDirect, and official publications of the Indonesian Ministry of Health. The selected literature included research articles, review articles, clinical guidelines, and relevant reference books. The review found that acute pharyngitis is predominantly caused by viral infections, although Group A Streptococcus (GAS) remains the most important bacterial pathogen due to its potential complications. Acute laryngitis is mainly caused by viral infections and is generally self-limiting. The diagnosis is made by gathering medical history, conducting a physical check, and performing additional tests if necessary. Treatment relies on the root cause and consists of supportive care, measures to ease symptoms, and antibiotic treatment in certain situations. Appropriate diagnosis and rational management are essential to prevent complications and improve patient outcomes.